Micro-mechanical properties of oak wood and comparison with standard-sized samples - Büyüksarı, Ümit; As, Nusret; Dündar, Türker; Korkmaz, Ogün (Maderas. Ciencia y Tecnología, 2017)
The aim of this study was to investigate micro-mechanical properties of Oak (Quercus petraea) wood and to compare with standard-size test specimens values. Bending strength, modulus of elasticity in bending, compression strength and tensile strength were determined using micro- and standard-size mechanical test samples. In the micro- and standard size samples, bending strengths were evaluated as 71,2 MPa and 99,4 MPa, modulus of elasticity in bending as 2741,3 MPa and 11394,1 MPa tensile strengths as 98,7 MPa and 93,8 MPa and compression strengths as 45,4 MPa and 46,6 MPa respectively. The results showed that the bending strength, modulus of elasticity and compression strength of the micro-size samples were lower compared to the standard-size samples, while the tensile strength was higher in the micro-size samples. The compression strength values of micro- and standard-size samples were not significantly different. The regression analyses indicated a positive linear regression between the mechanical properties of micro- and standard-size samples. Micro-size specimens can be used to estimate the mechanical properties of Oak wood when obtaining standard-size specimens is not possible. PDF XML